Aerobic exercise alone results in clinically significant weight loss for men and women: Midwest exercise trial 2123. (16th April 2013) - Donnelly, Joseph E.; Honas, Jeffery J.; Smith, Bryan K.; Mayo, Matthew S.; Gibson, Cheryl A.; Sullivan, Debra K.; Lee, Jaehoon; Herrmann, Stephen D.; Lambourne, Kate; Washburn, Rik A.
Abstract: Exercise is recommended by public health agencies for weight management; however, the role of exercise is generally considered secondary to energy restriction. Few studies exist that have verified completion of exercise, measured the energy expenditure of exercise, and prescribed exercise with equivalent energy expenditure across individuals and genders. Objective: The objective of this study was to evaluate aerobic exercise, without energy restriction, on weight loss in sedentary overweight and obese men and women. Design and Methods: This investigation was a randomized, controlled, efficacy trial in 141 overweight and obese participants (body mass index, 31.0 ± 4.6 kg/m 2 ; age 22.6 ± 3.9 years). Participants were randomized (2:2:1 ratio) to exercise at either 400 kcal/session or 600 kcal/session or to a nonexercise control. Exercise was supervised, 5 days/week, for 10 months. All participants were instructed to maintain usual ad libitum diets. Because of the efficacy design, completion of ≥90% of exercise sessions was an a priori definition of per protocol, and these participants were included in the analysis. Results: Weight loss from baseline to 10 months for the 400 and 600 kcal/session groups was 3.9 ± 4.9 kg (4.3%) and 5.2 ± 5.6 kg (5.7%), respectively, compared with weight gain for controls of 0.5 ± 3.5 kg (0.5%) ( P < 0.05). Differences for weight loss from baseline to 10 months between the exercise groups and differences between men and women within groups were not statistically significant. Conclusions: Supervised exercise, with equivalent energy expenditure, results in clinically significant weight loss with no significant difference between men and women.